2010
DOI: 10.1097/pai.0b013e3181e78ff8
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Pax-2 and Renal Cell Carcinoma Marker Immunohistochemistry in Distinguishing Papillary Renal Cell Carcinoma From Nonrenal Cell Neoplasms With Papillary Features

Abstract: PAX-2, a homeogene expressed during kidney development, has been studied as a marker of renal origin in both primary and metastatic clear cell renal cell carcinoma (RCC), but not in papillary neoplasms or in comparison with RCC marker (RCCma). We studied immunohistochemical expression of PAX-2 and RCCma in 24 papillary RCC (PRCC) and 66 nonrenal cell papillary neoplasms (NRCPN) from a variety of organs. Of the PRCC, 16/24 (67%) were positive for PAX-2; 23/24 (96%) were positive for RCCma. Of the NRCPN, 9/66 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
1
26
0
2
Order By: Relevance
“…Among tumors, PAX 2 has been reported to be expressed in the epithelial neoplasms of these organs, the embryogenesis of which is under the control of this transcription factor. These include all subtypes of renal cell carcinomas [158][159][160] and serous carcinomas of the ovary [160][161][162]. The percentage of PAX 2 positivity reported in metastatic clear cell renal cell carcinomas in different series has ranged from 49% to 85% [153,160,163] and, for serous carcinomas, 27% to 67% of the cases investigated [160][161][162].…”
Section: Paxmentioning
confidence: 95%
“…Among tumors, PAX 2 has been reported to be expressed in the epithelial neoplasms of these organs, the embryogenesis of which is under the control of this transcription factor. These include all subtypes of renal cell carcinomas [158][159][160] and serous carcinomas of the ovary [160][161][162]. The percentage of PAX 2 positivity reported in metastatic clear cell renal cell carcinomas in different series has ranged from 49% to 85% [153,160,163] and, for serous carcinomas, 27% to 67% of the cases investigated [160][161][162].…”
Section: Paxmentioning
confidence: 95%
“…39 In a combined review of 132 cases of primary and 53 metastatic ovarian serous carcinomas from six published studies, 63 (48%) and 23 (43%), respectively, were reported to be PAX2 positive. 14,31,[35][36][37][38] In addition, 2 (29%) of the 7 primary peritoneal serous carcinomas that have been investigated for PAX2 expression were positive for this marker. 31 That only 8 (53%) of the 15 primary and 17 (57%) of the 30 metastatic ovarian serous carcinomas in the present investigation were PAX2 positive indicates that the sensitivity of this marker for serous carcinomas is lower than that of PAX8.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 PAX2 null mice of both sexes completely lack the entire genital tract. 33 Among ovarian carcinomas, PAX2 expression has been reported to be often expressed in serous (27-100%), 14,[35][36][37][38] endometrioid (40%), 38 and clear cell (43%) carcinomas. 39 In a combined review of 132 cases of primary and 53 metastatic ovarian serous carcinomas from six published studies, 63 (48%) and 23 (43%), respectively, were reported to be PAX2 positive.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Several studies, each of which is devoted exclusively to either PAX2 or PAX8, have documented their expression in ovarian tumors. 11,[20][21][22][23] These studies further suggest a similar pattern of expression for PAX2 and PAX8 in these ovarian tumors. Nevertheless, a comprehensive direct combination of these 2 markers is not available, leaving several pertinent diagnostic issues unresolved, such as their comparative diagnostic sensitivity and specificity in ovarian serous tumors and ovarian mucinous tumors.…”
mentioning
confidence: 88%